Interdisciplinary approach to defining outdoor places of knowledge work: quantified photo analysis - Herneoja, Aulikki; Rönkkö, Emilia; Haapakangas, Annu; Malve-Ahlroth, Sara; Oikarinen, Essi; Hosio, Simo (Frontiers in Psychology, 2023)
Introduction. Working outdoors is an emerging, sparsely studied phenomenon in knowledge work. Office tasks have traditionally been considered to belong to indoor environments. The worldwide pandemic of COVID-19 has increased and changed attitudes towards multi-locational working. The aim of this method paper is two-fold. Firstly, to define for interdisciplinary context outdoor environments when they are used as places of outdoor knowledge work. And secondly, to quantify the thematic photo analysis to support interdisciplinary understanding of the places of outdoor knowledge work. Methods. The review of literature has been one of the methods to support the interdisciplinary approach of this article. The photographs of outdoor knowledge workplaces and views from the workstations are studied through photo analysis customised from the existing press photograph analysis. Results. Firstly, we defined outdoor environments when used as places of outdoor knowledge work, as unconditioned outdoor or semi-outdoor places (opposite to closed indoor spaces with stable, conditioned indoor climate) providing favourable action possibilities (affordance) as sources of comfort and mitigating unfavourable conditions for example by microclimatic solutions. Secondly, we focused on photo analysis. The proposed model is based on journalistic photo analysis PPSA (Kedra 2013), and the pOKW model (Herneoja et al. 2022), which have been further developed in this paper to pOKW2 model for analysing mobile-based collected self-reported photographs by the occupants. In this pOKW2 model, the photographs would have time-location information enabling the combining of data from other datasets and thereby reducing the number of characteristics to be analysed from the photograph. We proposed rating (in numeric form) to detect the favourable and unfavourable characteristics in the photographs most likely supporting or hindering conditions of outdoor knowledge work. This quantification would enable the use of machine-vision analysis and would support handling large quantities of photographs and their combination with other data sets in interdisciplinary research. Discussion. The quantification of the photo analysis (pOKW2) includes the readiness to combine the analysis results with other time-location-specific datasets in an interdisciplinary research collaboration to advance our understanding of latent action possibilities for outdoor knowledge work.